A Study of Female Sex Workers in Industrial Areas of the Sukabumi District, 2016 - Susanna, Dewi; Eryando, Tris; Pratiwi, Dian; Hendayana, Dian (KnE Life Sciences, 2018)
HIV AIDS cases have increased, partly due to the practicing of prostitution by female sex workers (FSW). This study examines FSW and their gathering places (i.e. FSW “hotspots”) in the Sukabumi District. It is a cross-sectional study, in which primary data was collected via observations, interviews and participatory mapping by key populations, while secondary data was obtained from the records of the Sukabumi AIDS Control Commission. In 2015, there were 80 FSW hotspots in 27 of the 47 districts in Sukabumi. Direct FSW accounted for 40% of cases, with the remaining 60% being Indirect FSW. By August 2016, numbers of Indirect FSW were found to have increased, with 24 hotspots around factories. In addition, 39 new cases of HIV/AIDS were observed in the population in 2016. FSW tend to use the internet to market their services because this is considered safer, easier and more profitable than using a pimp. The spread of HIV/AIDS becomes more difficult to track, however, when the internet is the main source of communication, and intervention also becomes more problematic. It is necessary to offer preventative measures upstream for adult males who have sexual intercourse with FSW and are at risk of contracting HIV. The disease can also be transmitted from husband to wife, so methods of preventing partners from being infected need to be considered.